2017
DOI: 10.1007/978-3-319-53547-0_2
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Parallel Wiener-Hammerstein Systems Using Tensor Decomposition of Volterra Kernels

Abstract: Providing flexibility and user-interpretability in nonlinear system identification can be achieved by means of block-oriented methods. One of such block-oriented system structures is the parallel Wiener-Hammerstein system, which is a sum of Wiener-Hammerstein branches, consisting of static nonlinearities sandwiched between linear dynamical blocks. Parallel Wiener-Hammerstein models have more descriptive power than their single-branch counterparts, but their identification is a non-trivial task that requires ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Palm (1978Palm ( , 1979 shows that a wide class of Volterra systems can be approximated arbitrarily well using a parallel Wiener-Hammerstein model structure. Dreesen et al (2017) present an identification method based on the decomposition of Volterra kernels.…”
Section: Parallel Wiener-hammerstein Structurementioning
confidence: 99%
“…Palm (1978Palm ( , 1979 shows that a wide class of Volterra systems can be approximated arbitrarily well using a parallel Wiener-Hammerstein model structure. Dreesen et al (2017) present an identification method based on the decomposition of Volterra kernels.…”
Section: Parallel Wiener-hammerstein Structurementioning
confidence: 99%
“…If there are at least two slices of G that do not contain any missing values, a GEVD can be computed of the subtensor consisting of these slices to partially initialize the optimization-based method. From the decomposition of G an estimate G (n) is obtained, which can be used to find the original circulant factors as described above in (6).…”
Section: Algorithm and Uniquenessmentioning
confidence: 99%
“…A Wiener-Hammerstein system is defined as a static nonlinear block sandwiched between two linear time-invariant FIR filters and can be identified by first estimating a Volterra kernel from input/output data and then computing its CPD. This idea was extended to parallel Wiener-Hammerstein systems in [6]. It is shown that the estimated Volterra kernels admit a structured tensor decomposition with almost all block-circulant factors.…”
Section: Parallel Wiener-hammerstein System Identificationmentioning
confidence: 99%
See 2 more Smart Citations